Force field and IR intensity calculations of aniline and transition metal(II) aniline complexes - Akalın, Elif; AKYÜZ, SEVİM (Elsevier, 1999)
A complete interpretation of the vibrational spectrum of aniline was carried out on the basis of normal coordinate analysis. The reliable force field and electro-optical parameters of aniline was determined by refinement in order to fit in the calculated wavenumbers and intensities of NH2- and ND2-aniline molecules with the experimental values. The geometrical parameters of free aniline were taken from experimental results. The initial force field parameters of aniline were refined from the corresponding parameters of benzene molecule. The initial values of bond dipole moments of the molecule were calculated by PM3 method. The force field of transition metal (II) aniline complex was determined by refinement of aniline force field. Coordination effect on aniline modes are interpreted in terms of changes in hybridization about the nitrogen atom.
Keywords: Normal coordinate analysis; Aniline; Aniline complex; IR spectrum; Force field; Electro-optical parameters